Opportunities and challenges in Philippine local governance of public health - Bautista, Victoria A. (Philippine Journal of Public Administration, 2008)
Public health is one of the primary concerns in the Philippines, especially in the marginalized sector. It does not only entail the curative aspect of health but the promotion and prevention of diseases. There are opportunities in governance of public health in local government units (LGUs) and challenges for improvement. Devolution of powers, institution of basic needs approach and popularization of the empowerment approach at the local level are some of the opportunities. The role of local executives in delivering quality services and budget allocation are the priority areas for improvement. There is a need for convergence of LGUs, civil society groups, nongovernment organizations in pursuing public health advocacy and mitigating the prevailing problems and threats.